The differences of movement between children at risk of developmental coordination disorder and those not at risk - Adrián Agricola; Rudolf Psotta; Reza Abdollahipour; Miriam Palomo Nieto (Palacký University Olomouc, 2015)
Background: Developmental coordination disorder (DCD) is a syndrome unexplained by medical condition, which is marked by defects in the development of motor coordination. Children with this impairment are more dependent on visual information to perform movements than their typically developing (TD) peers. Objective: The main aim of the research was to create a checklist for the evaluation of the head and limb movement while walking. After that, based on this tool, to find differences in the movement of various body segments in children at risk of DCD (DCDr) compared to typically developing children under different visual conditions. Methods: A total of 32 children aged 8.7 ± 1.1 years participated in this study. The Movement Assessment Battery for Children - 2nd edition (MABC-2) was used to make a classification of motor competence level of the participants. PLATO goggles were used to make four different visual conditions. All trials were recorded. Based on the video analysis we completed a qualitative checklist. Results: The analysis between the children from the DCDr group and TD children showed significant differences in the head (p = .023) and the arm (p = .005) movements, in body position (p = .002) and total summary score (p = .001). The main effects of visual conditions showed significant differences in all cases; in the head (p = .015), with the arm (p = .006), trunk (p =  .009), leg (p = .001) movements, in body position (p = .001) and also in the total summary score (p = .001). The interaction between groups and visual conditions was significant in leg movements (p = .007) and body position (p = .002). Conclusions: This study has shown which movements of body segments are most affected by different visual conditions and how children at risk of DCD are dependent on visual perception.